Adjunctive Local Delivery of Aloe Vera Gel in Patients With Type 2 Diabetes and Chronic Periodontitis: A Randomized, Controlled Clinical Trial. Issue 3 (1st March 2016) - Pradeep, A.R.; Garg, Vibhuti; Raju, Arjun; Singh, Priyanka
Abstract : Background: Herbal agents such as Aloe vera (AV) have been used in medical and dental therapy for thousands of years. AV has anti‐inflammatory, antioxidant, antimicrobial, hypoglycemic, healing‐promoting, and immune‐boosting properties. This study aims to investigate the clinical effectiveness of locally delivered AV gel used as an adjunct to scaling and root planing (SRP) in the treatment of patients with type 2 diabetes mellitus (T2DM) and chronic periodontitis (CP). Methods: Sixty patients with probing depth (PD) ≥5 mm and clinical attachment level (CAL) ≥3 mm were randomly divided into two groups. All patients underwent SRP. Placebo gel was locally delivered to group 1 and AV gel to group 2. Full‐mouth plaque index (PI), modified sulcus bleeding index (mSBI), PD, and CAL were recorded at baseline and 3 and 6 months. Results: Patients in group 2 showed significantly greater mean reductions in PI, mSBI, and PD and mean gain in CAL compared with those in group 1 from baseline to 3 months. Gain in CAL was significantly greater in group 2 at all time intervals versus group 1. Conclusion: Adjunctive use of locally delivered AV gel, in comparison to locally delivered placebo gel, is associated with greater reduction in PI, mSBI, and PD as well as more gain in CAL in patients with T2DM and CP.